Palliative care training addressed to hospital healthcare professionals by palliative care specialists: a mixed-method evaluation - Giovanna Artioli; Gabriele Bedini; Elisabetta Bertocchi; Luca Ghirotto; Silvio Cavuto; Massimo Costantini; Silvia Tanzi (BMC Palliative Care, 2019)
Abstract Background Despite the great advances in the concept of palliative care (PC) and its benefits, its application seems to be delayed, leaving unfulfilled the many needs of patients and family members. One way to overcome this difficulty could be to develop a new training programme by palliative care specialists to improve PC primary skills in healthcare professionals. The aim of this study was to evaluate the training’s impact on trainees within a hospital setting using Kirkpatrick’s and Moore’s models. Methods We adopted a mixed-method evaluation with concurrent triangulation. The evaluation followed the first three steps of Kirkpatrick’s and Moore’s models and included a pre- and post-training evaluation through self-administered questionnaires and focus groups. We used the McNemar statistical test. Results The results highlighted the significant amount of knowledge acquired by the hospital professionals after training, in terms of increasing their knowledge of palliative care and in terms of the change in meaning that they attributed to phenomena related to chronicity and incurability, which they encounter daily in their professional practice. In both quantitative and qualitative research, the results, in synthesis, highlight: (i) the development of a new concept of palliative care, centred on the response to the holistic needs of people; (ii) that palliative care can also be extended to non-oncological patients in advanced illness stages (our training was directed to Geriatrics and Nephrology/Dialysis professionals); (iii) the empowerment and the increase in self-esteem that healthcare professionals gained, from learning about the logistical and structural organization of palliative care, to activate and implement PC; (iv) the need to share personal aspects of their professional life (this result emerges only in qualitative research); (v) the appreciation of cooperation and the joining of multiple competences towards a synergistic approach and enhanced outcomes. Conclusion It is necessary to further develop rigorous research on training evaluation, at the most complex orders of the Kirkpatrick and Moore models, to measure primary PC skills in health care professionals. This will develop the effectiveness of the integration of I- and II-level palliative care competencies in hospitals and improve outcomes of patients’ and families’ quality of life.